Implementation of Word of Mouth Marketing (WOMM) Quality in Reveling Nasabah Interest in PPR Products with SWOT Analysis: (BTN KCP Syariah Setia Budi) - Manurung, Ibnu Syawali; Yanti, Nursantri; Nasution, Muhammad Lathief Ilhamy (Ilomata International Journal of Management, 2024)
This study aims to analyze the implementation of Word of Mouth Marketing (WOMM) quality in increasing customer interest in Home Ownership Loan (PPR) products at BTN KCP Syariah Setia Budi using SWOT analysis. This research employs SWOT analysis (Strenght, Weakness, Opportunities, Threats) as its foundational framework. The results indicate that WOMM has significant potential to attract customer interest, particularly through the strength of satisfied customers' credibility and the superior quality of services. Major opportunities are also identified in the growth of digital and social media and the increasing trust in sharia financial products. However, challenges include dependence on customer perceptions, limited control over WOMM messages, and intense market competition. With the right strategies, such as enhancing service quality, leveraging social media, and encouraging positive testimonials, BTN KCP Syariah Setia Budi can optimize the positive impact of WOMM to strengthen the market position of their PPR products.